PENGGUNAAN PESTISIDA NABATI MENGENDALIKAN HAMA-HAMA PADI MERAH (Oryza nivara L.) DI DUSUN SOPORARU, TAPANULI UTARA, SUMATERA UTARA - Ameilia Zuliyanti Siregar; Tulus Tulus; Kemala Sari Lubis (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2021)
Locally specific Natabo brown rice was identified in Pangaribuan Subdistrict, North Tapanuli, where the attack of stem borer, brown planthoppers, leafhoppers and stink bugs affects rice productivity. The alternative step to control pests in a biological used by biology pesticides to increase productivity and food security. This research was conducted for eight months during March to October 2020, with a survey stage, inventory of pests in the fields using the purposive random sampling method in Soporaru backwoods, Sigotom Julu Village, Pangaribuan District, North Tapanuli. The application of biology pesticides consists of 5 treatments, namely: B0 (Control, without application); BP1 (neem leaves, galangal, lemongrass, detergent, water); BP2 (soursop leaves, galangal rhizome, garlic, detergent, water); BP3 (soursop leaves, detergent, water) and BP4 (kenikir leaves, marigold flowers, Zinnia flowers). The composition of insects consist of 8 order, 26 familes, totalpopulation were 1.080 individuals.The calculation of the Margallef species richness index (Rp=7.25; Rc=7.15), the Evenness evenness index (Ep= 0.62; Ec=0.57) and the Shannon Wiener diversity index (Hp'= 2.38; Hc’=2.12). The parameters of temperature, humidity, rainfall) are calculated. The use of biology pesticides has strategic potential in controlling the dominant pests of rice in the future.